2008
DOI: 10.1086/592055
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphic Variability in the Interleukin (IL)–1β Promoter Conditions Susceptibility to Severe Malarial Anemia and Functional Changes in IL‐1β Production

Abstract: Interleukin (IL)-1β is a cytokine released as part of innate immune response to Plasmodium falciparum. Since the role of IL-1β polymorphic variability in conditioning the immunopathogenesis of severe malarial anemia (SMA) remains undefined, relationships between IL-1β promoter variants (-31C/T and -511A/G), SMA (Hb<6.0 g/dL), and circulating IL-1β levels were investigated in parasitemic children (n=566) from western Kenya. IL-1β promoter haplotype -31C/-511A (CA) was associated with increased risk of SMA (Hb<6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 46 publications
3
40
1
Order By: Relevance
“…Our previous investigations in the cohort investigated here demonstrated that multi-site haplotypes are highly informative allelic markers that can reveal associations with malaria disease outcomes not identifiable with single polymorphisms (Ouma et al 2008a; Ouma et al 2008b). As such, the role of FcγRIIA-131H/R and FcγRIIIB-NA1/NA2 haplotypes in mediating susceptibility to SMA and functional changes in IFN-γ levels were examined in children with acute malaria (n=528; 3-36 mos.)…”
Section: Introductionmentioning
confidence: 81%
“…Our previous investigations in the cohort investigated here demonstrated that multi-site haplotypes are highly informative allelic markers that can reveal associations with malaria disease outcomes not identifiable with single polymorphisms (Ouma et al 2008a; Ouma et al 2008b). As such, the role of FcγRIIA-131H/R and FcγRIIIB-NA1/NA2 haplotypes in mediating susceptibility to SMA and functional changes in IFN-γ levels were examined in children with acute malaria (n=528; 3-36 mos.)…”
Section: Introductionmentioning
confidence: 81%
“…with SMA being the single severe disease manifestation in regions of holoendemicity. Utilizing such an approach, focusing specifically on innate immune response genes in parasitized children, we have identified a number of genes that have significant relationships with both the risk of developing SMA and functional changes in their respective gene products (4,37,38). To extend these results, we investigated two functional promoter polymorphisms in IL-18 at positions Ϫ137 and Ϫ607 in children with and without SMA.…”
Section: Discussionmentioning
confidence: 99%
“…Based on historical presence of the disease, malaria has exerted a large impact on the human genome such that potentially harmful variants are preserved, largely because of the advantage offered in heterozygous individuals that are often protected from severe, complicated, and fatal malaria (14,19,21). Studies in our laboratory focused on variations in key cytokine genes have demonstrated associations between polymorphisms and SMA (4,37,38).…”
mentioning
confidence: 99%
“…Sustained release of IL-1β, as experienced in malaria, has the potential of inducing several hematologic and immunologic anomalies with anemia as a candidate [47,48]. However, cytokine IL-1β has a protective role in certain haplotypes, which are predisposed to produce higher levels of this cytokine and prevents anemia development [49].…”
Section: Severe Malarial Anemia and The Inflammasomementioning
confidence: 99%